Polarographic Behaviour of {3-Hydroxy-3-oTolyl-1-(p-Carboxyphenyl) Triazene} (HOTCPT) ion and (3-Hydroxy-3-Ethyl-1-(p-Carboxyphenyl) Triazene} (HECPT) Ion with Cadmium - Kumar Lohiya, Rajendra; Lal Prathihar, Panna; Singh, R.V.; Mukherji, S.K. (Asian Journal of Chemistry, 2010)
The overall formation constants of the hydroxy triazene complexes were determined polarographically by DeFord and Hume's method as modified by Irving. These compounds have been synthesized for the first time. The percentage distribution of cadmium present in various forms as a function of ligand concentration was also calculated..